2011
DOI: 10.1586/erc.11.170
|View full text |Cite
|
Sign up to set email alerts
|

Common arterial trunk: review of surgical strategies and future research

Abstract: Common arterial trunk is a congenital malformation that is relatively uncommon, representing 0.21-0.34% of congenital heart disease. Natural history, if not treated, leads to early death. Cardiac surgery has been modifying its natural course during the last 30 years by prolonging the lifespan of patients affected. Despite surgical mortality improvements over the last 10 years, morbidity still remains high, mainly due to the age of the patient, associated heart lesions, the evolution of truncal valve function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…In contrast with previous studies based on early CAT operations, 11,13 in our more recent series, we found that surgical repair of CAT without a valved conduit was not associated with an increased risk of mortality. As in previous studies, we also found that coronary anomalies [1][2][3][4]8 and CAT with interrupted aortic arch [5][6][7][8] were independent risk factors for mortality.…”
Section: Mortalitysupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast with previous studies based on early CAT operations, 11,13 in our more recent series, we found that surgical repair of CAT without a valved conduit was not associated with an increased risk of mortality. As in previous studies, we also found that coronary anomalies [1][2][3][4]8 and CAT with interrupted aortic arch [5][6][7][8] were independent risk factors for mortality.…”
Section: Mortalitysupporting
confidence: 88%
“…Risk factors for mortality related to common arterial trunk (CAT) include coronary anomalies leading to ostial or luminal coronary narrowing or stenosis, [1][2][3][4] truncal valve dysfunction, 5,6 and interrupted aortic arch [5][6][7] among the most frequently reported. In addition, low weight at surgery 8,9 and high pulmonary vascular resistance are also associated with a greater risk of mortality.…”
Section: Perspectivementioning
confidence: 99%
“…4 SV heart defects can be divided into four types according to the morphological structure: Type A, the left ventricular main chamber is dominant; Type B, the right ventricular main chamber is dominant; Type C, the ventricular septum is absent, and the left and right ventricular structures constitute the ventricular cavity; and Type D, indeterminate. 5 Unlike echocardiography, three-dimensional ultrasound can visually display the internal structure of the heart, thus improving the accuracy of preoperative diagnosis, and is of great significance in the selection of surgical methods and the assessment of prognosis. 6 We reviewed literature reports of SV heart defect cases involving patients over 13 years of age without surgical intervention and summarized the common characteristics that were correlated to the long-term survival of the patients (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…It is a rare lesion, accounting for 0.21-0.34% of congenital heart disease with an incidence of 0.03-0.05 cases per 1000 live births(2). Prior to availability of operative correction, children with TA demonstrated 80% mortality in the first year of life(3).…”
Section: Introductionmentioning
confidence: 99%